Integrating economics lessons into Snake and Ladder game: an innovation approach to sustainable education - Ab Rani, Nor Zuriati Amani; Nik Hassan, Nik Suriati; Che Hamzah, Hamnah (2025)
The integration of sustainable education through game-based learning strategies, such as the traditional Snake and Ladder game into the economics lessons has shown promising results in enhancing student engagement and understanding. This study explores the application of the Snake and Ladder game as an interactive pedagogical tool to facilitate the innovation of learning economic concepts among students. The game is adapted to include questions and challenges related to theories of economics, such as supply and demand, cost and production, market structures, and other core economic topics. The integration of this game into classroom instruction has shown significant positive impacts on students’ learning experience. It makes the learning process more fun and enjoyable, captures students’ attention, and reduces classroom boredom. Furthermore, it encourages active participation and collaborative learning and improves students' motivation and interest in the subject. The findings indicate that this method not only enhances understanding and retention of knowledge but also creates a lively and student-centred classroom environment. In conclusion, the Snake and Ladder game proves to be an effective and engaging pedagogical approach in making the subject of economics more accessible and less intimidating for learners. This innovation points out the importance of gamification as a tool for advancing sustainable education and improving learning outcomes in economics lessons.